A study to assess the clinical probability of deep vein thrombosis among patients admitted in Maharishi Markandeshwar institute of medical sciences and research, Mullana, Ambala, Haryana - Rathore, Ghanshyam; Saklani, Manisha (International Journal of Research in Medical Sciences, 2024)
Background: Deep vein thrombosis (DVT) is a major cause of morbidity and mortality worldwide, with an estimated yearly prevalence of 1 in 1,000 and about 350,000 new cases in the USA annually. DVT involves a blood clot in deep veins, primarily in the legs or pelvis. Its significance lies in clot migration, which can lead to life-threatening pulmonary embolism (PE). The development of DVT is summarized by Virchow's Triad: venous stasis, endothelial injury, and hypercoagulability. Methods: The current study approach was the quantitative approach and descriptive design. The study sample included patients admitted in the ward of MMIMSR, Ambala, Haryana Results: In the study, 72.1% of participants were in the "no special risk" category. The "average desirable" category had 65.6% of participants. For mobility, both "limited (uses aids, self)" and "complete bed rest" categories had 27% each. The "no injury" category included 58.1%. Swelling was noted in 81.9%, and warm skin in 65.6%. Significant associations with DVT were found for age, ward, and illness duration (p<0.05). The highest risk levels for DVT were "moderate risk" (41.4%) and "high risk" (34%), with "no risk" and "low risk" categories being smaller. Conclusions: This study concludes that hospitalized patients may risk developing DVT. Screening should be performed using Dr. Ricky Autar’s DVT risk assessment tool. Preventive interventions and personalized risk stratification are crucial for moderate and high-risk DVT categories. Timely surveillance, education, AI diagnostics, wearable tech, and policy changes can improve early detection, treatment, and management of DVT.